α-Galactosylceramide (KRN7000) suppression of chemical- and oncogene-dependent carcinogenesis - Hayakawa, Yoshihiro (National Academy of Sciences, 2003)
Recent studies have revealed significant efficacy of the marine sponge glycolipid, α-galactosylceramide (α-GalCer), in treatment of experimental metastatic cancers, infections, and autoimmune diseases. However, the capacity of α-GalCer to prevent tumor development had never, to our knowledge, been evaluated in mouse models of chemical- and oncogene-dependent carcinogenesis. In this study, we demonstrate that long-term administration of soluble α-GalCer, spanning the time of tumor initiation, inhibits primary tumor formation in three different models: methylcholanthrene-induced sarcomas, mammary carcinomas in Her-2/neu transgenic mice, and spontaneous sarcomas in p53(–)(/)(–) mice. Weekly treatment of mice with α-GalCer maintained lymphoid tissue natural killer cell and T cell activation and elevated serum IFN-γ and IL-4 concentrations. Consistent with the antimetastatic activity of α-GalCer, prevention of methylcholanthrene-induced sarcoma was IFN-γand tumor necrosis factor-related apoptosis-inducing ligand dependent, but not perforin-dependent. Taken together, our results demonstrate that NK1.1(+)αβTCR(+) cell-based immune therapy can inhibit primary tumorigenesis.